Characterization of the Synergistic Antioxidant Activity of Epigallocatechin Gallate (EGCG) and Kaempferol - Qiang Zhang; Junkun Pan; Hui Liu; Zhonggao Jiao (Molecules, 2023)
Epigallocatechin gallate (EGCG) and kaempferol exhibit cellular antioxidant activity; however, their interactive effects in terms of antioxidant actions and underlying mechanisms remain unclear. In this study, their cytoprotective effects were examined against 2,2-azobis (2-amidinopropane) dihydrochloride solution (ABAP)-induced oxidative stress in HepG2 cells. The results showed that the median effective dose (EC50) of the EGCG and kaempferol (6:1.5, c/c) combination was 3.4 ± 0.1 μg/mL, with a combination index (CIavg) value of 0.54, which represented a significant synergistic effect. Further experiments proved that the combined pretreatment with EGCG and kaempferol exerted protective effects by suppressing reactive oxygen species (ROS) generation, upregulating cellular antioxidant enzyme activities (superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px)) in a dose-dependent manner. The mechanism of synergistic antioxidant effects of EGCG combined with kaempferol may be due to the up-regulation of higher antioxidant enzyme activities that improve the antioxidant capacities and balance the cell oxidative stress. The synergistic antioxidant effect of EGCG and kaempferol can provide a theoretical basis for the development of formulas of functional food ingredients.